Microbiota profile associated with neonatal sepsis in reference maternity in State of Pará, Amazon, Brazil (Research, Society and Development, 2024)
Neonatal sepsis is a clinical syndrome that affects neonates due to the transmission/colonization of microbial agents during pregnancy or childbirth, unregulated development of the microbiota of the skin and gastrointestinal tract or through exposure to catheters during hospitalization. To determine the pathogenic profile implicated in neonatal sepsis and its sensitivity/resistance to antimicrobials. The study analyzed 803 medical records of neonates born between 2020 and 2022 at the reference maternity hospital in the State of Pará, Amazon, Brazil. They had a clinical diagnosis of sepsis with positive blood cultures. The prevalence of the disease was 13.77%, death 18.80% and lethality 19.95%. Staphylococcus epidermidis was the most frequent (56.29%) and was resistant to oxacillin and clindamycin. Klebsiella pneumoniae was observed in 36.57% of the cases and associated with death, it proved to be multiresistant to Ampicillin, Cefepime, Ceftazidime, Cefuroxime and Ceftriaxone. Sensitivity was observed for Meropenem, Amikacin and Imipenem. Conclusion: Estimating the prevalence of circulating microbial profiles that cause neonatal sepsis, as well as their resistance/sensitivity, was of paramount importance to support strategies that improve timely diagnosis and adequate treatment, avoiding the empirical and indiscriminate use of antibiotics.